Dance-writing and dramaturgy. Experiences of a workshop - Ruiz Mondragón, Laura (UNIVERSIDAD DE SONORA, 2021)
This text is part of the doctoral work "Research-action: dance-writing as a possibility of self-enunciation". For the practical part of the research, the Dance and writing workshop was given as a laboratory. What is presented in this article is a part of the analysis of what happened during the workshop. It delves into the operation of dramaturgy in the design of the sessions, in the organization of the individual and collective texts and dances that occurred during the laboratory, as well as in the assembly of the materials for presentation to an audience. Dramaturgy is the articulating tool to study the creative process in which each participant found a space for their own enunciation and the resonances that this had in the group. To address the analysis, the approaches of André Lepecki on dramaturgy and those of Laurence Louppe on score are taken as a starting point.